PENGARUH VIDEO PEMBELAJARAN AUDIO VISUAL DALAM MENGENALKAN BUNYI HURUF DALAM PEMBELAJARAN MEMBACA PERMULAAN - Beatrice, Benedicta; Aunurrahman, Aunurrahman; Linanarsih, Andini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determined the effect of learning videos on the ability to read words in children aged 5-6 years at Brother Nusa Indah Kindergarten, Pontianak. The research method used is an experiment with a quantitative approach with the type of research being Pre-Experimental Design One Group Pretest-Posttest. The research samples taken were all students in groups B1 and B2 in TK Pontianak as many as 23 children. The research instruments used were observation sheets and data collection.The tools used were observation techniques and documentation techniques. Based on the results of the analysis of the Wilcoxon Matched Pairs hypothesis test, it was found that Tcount T table with a value of 0.01 0.05, then H0 was rejected and Ha was accepted. So it can be concluded that there was an effect of video learning on reading skills for children aged 5-6 years at Brother Nusa Indah Kindergarten, Pontianak.